(untitled) (Research, Society and Development, 2023)
The objective of this study is to analyze the main complications arising from laparoscopic cholecystectomy (LC) and, as a secondary objective, to identify risk factors that lead to poor outcomes. Making it an even safer procedure for the patient. The study is a narrative review of research on CL. A search for articles was carried out in the Medical Literature Analysis and Retrievel System Online (MEDLINE) and Scientific Electronic Library Online (SciELO) databases with the following Health Sciences Descriptors (DeCS): Cholecystectomy Laparoscopic; Cholecystectomy; General Surgery; Intraoperative Complications; Risk Factors, totaling 20 articles selected from both databases. Articles were selected between the periods of 2009 to 2022, in English, Portuguese and Spanish, to increase the level of relevance and quality of the review. The main complications arising from performing LC are inability to tolerate pneumopertoneum or general anesthesia, impediments to the correct identification of anatomical structures, and the surgeon’s inexperience, even if they are minimal. Due to the advantages that the postoperative period has and the ease of handling, LC has rapidly expanded in surgical centers. However, the incidence of ductal and arterial lesions developed at the same rate, linked to the learning of the surgical community. Thus, even with minimal mortality and complication statistics, LC needs broad attention and awareness from the entire team, whether in asepsis or in basic safety concepts.